Effectiveness of Aquaponic Systems to Reduce Ammonia in Tilapia (Oreochromis niloticus) Culture - Hidayah, Muh Wahyu; Mangitung, Septina F.; Rusaini, Rusaini (FAPETKAN UNTAD, 2021)
This study was conducted to determine the ability of aquaponic systems using different numbers of water spinach (Ipomea aquatica) clumps in reducing ammonia in tilapia (Orechromis niloticus) culture. This study was designed in a Completely Randomized Design (CRD) with 5 treatments and 4 replicates, namely Treatment A (without water spinach), B (3 clumps of water spinach), C (6 clumps of water spinach), D (9 clumps of water spinach) and E (12 clumps of water spinach). This study was conducted for 60 days in November-December 2018 at the Fish Reproduction Laboratory, Brawijaya University, Malang. The results showed that the use of different numbers of water spinach clumps in the aquaponic system had a significant effect (P<0.05) on the reduction of ammonia and nitrite concentrations, but had no significant effect (P>0.05) on the reduction of nitrate and absolute growth of tilapia. The highest ammonia and nitrite reduction concentrations were found in the treatment of 12 water spinach clumps 84.31% and 69.88%, respectively.